MiR-139-3p is related to left ventricular hypertrophy and cardiomyocyte apoptosis in two-kidney one-clip hypertensive rats - Yang Xiaomin; Yu Hui; Hu Hai; Yue Jianwei; Tian Xuyang; Wang Cong; Yan Xulong; Sun Gang; Wang Zhanli (Archives of Biological Sciences, 2015)
MicroRNAs (miRNAs) are important post-transcriptional regulators of gene expression in many physiological and pathological processes. Previous studies have reported the role of miR-139-3p in cancer. However, its specific roles and functions in the heart undergoing hypertrophy have yet to be fully elucidated. In the present study, a significant upregulation of miR-139-3p expression was demonstrated in the left ventricular myocardium of two-kidney one-clip (2K1C) hypertensive rats using microarray and quantitative real-time PCR (qRT-PCR). Based on computational analysis, we observed that miR-139-3p can control the expression of mitogen-activated protein kinase 1 (MAPK1) as a target gene, which is essential for the induction of cardiac hypertrophy and cardiomyocyte apoptosis. This study provides first information that the highly expressed miR-139-3p might be closely involved in MAPK1-mediated cardiac hypertrophy and cardiomyocyte apoptotic processes in 2K1C rat.